Influence of the aluminum die casting process on PEEK layered CFRP in the manufacturing of a hybrid connection. Issue 1 (May 2021) - Marx, A; Schmid, A; Haubold, T; Pursche, L; Schiebel, P; Herrmann, A
Abstract: Lightweight design is used as a key technology in a variety of fields to achieve significant weight reduction. Due to its low density in combination with high strength, CFRP and aluminum are predestinated lightweight materials. However, the joining of this material combination is still performed using common technologies like adhesive or mechanical joining. A major challenge at the joining of this material combination is the corrosion behavior. Therefore a novel approach of a hybrid connection between CFRP and aluminum was developed by using the HPDC process of aluminum. During efficient HPDC process, a CFRP structure is recast with aluminum (AlSi10MnMg). To resist the shortly appearing temperature of 700 °C from the liquid aluminum melt, the CFRP is coated with a layer of PEEK. This leads to a material transition, which spatial separates CFRP and aluminum and a hybrid connection with tensile shear strengths up to 22 MPa. Within this work, the influence of the several processing steps on the PEEK layer and the structure of the CFRP was investigated. DSC and TGA results show no significant change on thermal properties of the PEEK. Imaging investigations show the appearance of heat induced volatilizations in the PEEK layer of the hybrid specimens after the HPDC process.